Low grade Gliomas Multi Modality Approach - AL-Shalchy, Ali K. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Gliomas are brain tumours of supporting tissue of the brain. The management of low grade glioma is still a great debate ranges from just follow up to extensive surgery followed by DXT, with or without chemothery.Patients and Methods: 282 patients taken from neuro-surgical hospital between 1980-1990, divided to 3 groups with different modality of management & follow up for 15 years.Results: the five years survival and symptomatic improvement was higher in the group managed by extensive surgery and DXT with or without cytoxic drugs followed by group managed by biopsy and DXT with or without cytoxic.Conclusion: management of low grade glioma symptoms & out come (survival) is best by extensive surgery & DXT with or with out cytotoxic, followed by biopsy & DXT with or without cytotoxic drugs.